Homeostasis in anorexia nervosa - Södersten, Per; Bergh, Cecilia; Zandian, Modjtaba; Ioakimidis, Ioannis (Frontiers in Neuroscience, 2014)
Brainstem and hypothalamic “orexigenic/anorexigenic” networks are thought to maintain body weight homeostasis in response to hormonal and metabolic feedback from peripheral sites. This approach has not been successful in managing over- and underweight patients. It is suggested that concept of homeostasis has been misinterpreted; rather than exerting control, the brain permits eating in proportion to the amount of physical activity necessary to obtain food. In support, animal experiments have shown that while a hypothalamic “orexigen” excites eating when food is abundant, it inhibits eating and stimulates foraging when food is in short supply. As the physical price of food approaches zero, eating and body weight increase without constraints. Conversely, in anorexia nervosa body weight is homeostatically regulated, the high level of physical activity in anorexia is displaced hoarding for food that keeps body weight constantly low. A treatment based on this point of view, providing patients with computerized mealtime support to re-establish normal eating behavior, has brought 75% of patients with eating disorders into remission, reduced the rate of relapse to 10%, and eliminated mortality.